Optical vortex sign determination using self-interference methods - Kurzynowski, Piotr; Borwińska, Monika; Masajada, Jan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We have proposed a simple method for determining the sign of optical vortex seeded in optical beam. Our method can be applied to any single optical vortex, also the one with topological charge magnitude higher than 1, as well as to the whole vortex lattice. The proposed method has been verified experimentally for all the cases.
Optica Applicata, Vol. 40, 2010, nr 1, s. 165-175
Keywords: optyka; optical vortex; interference; birefringence